Esophageal Mucosa Innervation in Children With Nonerosive Reflux Disease. (29th August 2021) - Nikaki, Kornilia; Lee, Chung; Ustaoglu, Ahsen; Alessandrella, Annalisa; Staiano, Annamaria; Woodland, Philip; Sifrim, Daniel
Abstract : INTRODUCTION: Esophageal mucosa innervation in adults with nonerosive reflux disease (NERD) is more superficial compared with healthy volunteers. We delineated the esophageal mucosal innervation in pediatric NERD and controls. METHODS: Distal and proximal pediatric esophageal biopsies were immunohistochemically stained with calcitonin gene-related peptide and transient receptor potential cation channel subfamily V member 1. RESULTS: Mucosal innervation was assessed in 18 controls (9M:9F, median age: 9 years) and 11 NERD patients (6M:5F, median age: 5 years). Calcitonin gene-related peptide positive nerve fibers were lying deep in the mucosa in both groups, P > 0.05 and did not coexpress transient receptor potential cation channel subfamily V member 1. DISCUSSION: The pediatric esophageal mucosa in NERD displays deep lying nerve fibers, in contrast to adults.